Isolation Of Endophytic Fungi From Aloe Vera Against Bacteria That Cause Digestive Tract Infections By TLC-Bioautography And Agar Diffusion - Ramadhana, Evi Rahma; Herwin, Herwin; Nuryanti, Siska (Journal Microbiology Science, 2024)
The Aloe vera plant, also known as the Lidah buaya plant, has antibacterial properties due to its secondary metabolites, which include alkaloids, flavonoids, tannins, and saponins. In this study, endophytic fungi from Lidah Buaya (Aloe vera) were isolated against bacteria that cause gastrointestinal tract infections using TLC-Bioautography and Agar Diffusion. In this study, 7 isolates of endophytic fungi were obtained, one of which was IFLB 1 which had potential as an antibacterial, purification of the endophytic fungi was carried out and then macroscopic examination was carried out on the fungi to see the colonies formed. After that, a screening test was carried out for isolates of endophytic fungi. Then the isolates that gave the best activity were reproduced and continued with the fermentation process for 14 days. The extraction results were then evaporated to obtain a thick extract and a Thin Layer Chromatography (TLC) Identification test was carried out in which the eluent used was chloroform: methanol (5:1). Then continued the TLC-Bioautographic Antibacterial Activity Test on Escherichia coli, Salmonella thypi, Shigella dysentriae and Vibrio cholerae bacteria and obtained 2 active spots with Rf1 = 0.78 and Rf2 = 0.30. While the results of testing the antibacterial activity using the Agar Diffusion method obtained the largest diameter of the inhibition zone at a concentration of 4% for Escherichia coli with an inhibition zone diameter of 15.80 mm, Salmonella thypi with an inhibition zone diameter of 14.90 mm, Shigella dysentriae with an inhibition zone diameter of 13 .85 mm and Vibrio cholerae with an inhibition zone diameter of 14.70 mm